Transit Team Case Study – Small Business Acquisition - Ebben, Jay; Johnson, Alec (Journal of Management Policy and Practice, 2018)
This case is intended for an undergraduate entrepreneurial finance course to illustrate how valuation and deal terms impact risk and reward potential. The case details the path of Mike Richter, who at the age of 27 is about to acquire an 18 million transportation company, where he has worked for the previous two years. Students are given details on an original and revised deal and asked to compare the two in terms of the risk to Mike in taking over the business.